PENGARUH PROMOSI PENJUALAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA IDJEN PREMIER SPORTS CLUB DI MALANG - Mila Yuni Pratiwi; Hendri Soekotjo; Triyonowati Triyonowati (Pascasarjana Universitas Halu Oleo, 2019)
This study discusses direct sales promotion and service quality to customer satisfaction and customer loyalty and indirect sales promotion to customer loyalty through customer satisfaction as an intermediate variable and indirectly affects service quality towards customer loyalty through customer satisfaction as an inter-variable. This study uses path analysis (path analysis), F test, t test and sobel test.The sampling technique in this study is a non probability sampling of 100 respondents. The results of this study indicate that sales promotion shows positive and significant impact on customer satisfaction, positive and significant service quality on customer satisfaction, positive and significant sales promotions on customer loyalty, service quality increases negatively and not significantly on customer loyalty, positive customer satisfaction and significance towards customer loyalty. In addition there is also an indirect between sales promotion to customer loyalty through customer satisfaction and there is an indirect between the quality of service to customer loyalty through customer satisfaction.Keywords: sales promotion, service quality, customer satisfaction, customer loyalty